Pollination operations and field organization in the territory of the Taza Province – Morocco - BOUBERRIA, ABDELOUAHED; Hammimi, Abdelhafid; Abahrour, Mohammed; Errafik, Mohammed (Journal of Humanities & Social Sciences, 2024)
In March 2020, the World Health Organization classified COVID-19 as a pandemic. This global crisis has affected every country, including Morocco. In this context, the Taza Province served as a scientific laboratory to address a social issue with a spatial and systematic approach, specifically focusing on the organization and process of vaccination.We aimed to address the issue of vaccination and field organization by examining territorial divisions as a mechanism to achieve social justice. Our research explored the structures of vaccination and the demographics of the targeted groups. Additionally, we tracked the chronological development of vaccination operations within the study area. We considered these operations essential for the population to mitigate the risks and impact of COVID-19.This article is the result of joint efforts with the National Center for Scientific and Technical Research (CNRST), conducted within the framework of projects examining the economic, social, and spatial repercussions of COVID-19.
Keywords: Covid-19; Taza Province; vaccination; field regulation